2021
DOI: 10.1016/j.visres.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-reversed binocular dot-pairs in random-dot stereograms for depth perception in central visual field: Probing the dynamics of feedforward-feedback processes in visual inference

Abstract: In a random-dot stereogram (RDS), the spatial disparities between the interocularly corresponding black and white random dots determine the depths of object surfaces. If a black dot in one monocular image corresponds to a white dot in the other, disparity-tuned neurons in primary visual cortex (V1) respond as if their preferred disparities become non-preferred and vice versa, reversing the disparity sign reported to higher visual areas. Reversed depth is perceptible in the peripheral but not the central visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…The perceptual impression was qualitatively different from that of seeing too many contour fragments crowded together like in visual crowding. In depth perception of random-dot stereograms in central vision, it has been demonstrated that stimulus components (from dichoptically contrast-reversed dots) that are normally vetoed (and thus invisible) can nevertheless enhance or sometimes degrade another perceptual outcome arising from other stimulus components (from dichoptically contrast-matched dots) ( Zhaoping, 2021 ). This manifests a complex interaction between the feedforward and feedback processes.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceptual impression was qualitatively different from that of seeing too many contour fragments crowded together like in visual crowding. In depth perception of random-dot stereograms in central vision, it has been demonstrated that stimulus components (from dichoptically contrast-reversed dots) that are normally vetoed (and thus invisible) can nevertheless enhance or sometimes degrade another perceptual outcome arising from other stimulus components (from dichoptically contrast-matched dots) ( Zhaoping, 2021 ). This manifests a complex interaction between the feedforward and feedback processes.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This faster deterioration suggests, according to the CPD, that top-down feedback is likely involved to achieve this hyperacuity feat. Indeed, at fovea, this acuity worsens with shorter viewing durations ( Westheimer and McKee, 1977 ), presumably because a shorter viewing hinders or prevents the feedback process to function (as suggested by an example of depth perception at fovea ( Zhaoping, 2021 )), and, if so, the CPD predicts that, at a more peripheral location, hyperacuity should suffer less from a shorter viewing duration. Many other visual discrimination tasks, on which human performance deteriorates with visual field eccentricity faster than suggested by a reduced V1 cortical magnification factor ( Strasburger et al, 2011 ), could be examined analogously in this light.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In order for a dACRDS to provide any sort of sensation of depth, special measures need to be taken: for example, for it to produce reversed depth at all, the dot density must be below 2% (Cumming et al, 1998 ); reversed depth perception can also occur when a dACRDS disk is shown surrounded by a dCRDS annulus in the central visual field (Aoki et al, 2017 ), but this reverse perception of depth also depends on the size of the gap between the two visual stimuli (Asher and Hibbard, 2018 ). Further, depth perception can be reversed when the temporal aspects of vision are exploited: when dACRDS mixed with zero-disparity dCRDS dot noise has been demonstrated to modulate (augment or degrade) depth perception, when it is flashed very briefly in the central visual field and the correlation turns during this short time (Zhaoping, 2021 ). Moving away toward the peripheral visual field where the spatial resolution drops considerably, dACRDS has also been demonstrated to elicit reversed depth perception when the stimulus is intentionally projected into this area (Zhaoping and Ackermann, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…When stimuli contained just a step edge in depth, the majority (67%) of participants who perceived depth in CRDS also perceived depth in the natural rather than reversed direction for ACRDS [ 17 ]. Finally, reversed depth in ACRDS has been reported to be more common when stimuli are presented in the periphery of the retinal image, rather than the centre [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brief presentations will tend to enhance the responses of the transient stereoscopic system, which may be important in the perception of depth from ACRDS [ 21 ]. Longer durations will support the effects of top-down feedback, and thus the reduction of perceived depth in ACRDS [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%